2007
DOI: 10.1158/1541-7786.mcr-06-0398
|View full text |Cite
|
Sign up to set email alerts
|

APC Mutations and Other Genetic and Epigenetic Changes in Colon Cancer

Abstract: Relationships between adenomatous polyposis coli (APC) mutations, BRAF V600E mutations, and the CpG island methylator phenotype (CIMP) in colon cancer have not been explored. In addition, controversies exist about the proportion of tumors with APC mutations in the mutation cluster region (MCR); how commonly APC, Ki-ras, and p53 mutations occur in the same tumor; and whether APC mutations occur in sporadic microsatellite-unstable tumors. The APC gene was therefore sequenced in 90 colonic adenocarcinomas previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 31 publications
15
91
0
4
Order By: Relevance
“…According to this finding, in accordance with Wang and Xavier's findings, CA 19-9 was identified as a significant independent prognostic predictor in our study (Filella et al, 1992;Wang et al, 2002). Also, in a recent study it was demonstrated that CA 19-9 was superior to CEA in post-operative follow-up (Samowitz et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to this finding, in accordance with Wang and Xavier's findings, CA 19-9 was identified as a significant independent prognostic predictor in our study (Filella et al, 1992;Wang et al, 2002). Also, in a recent study it was demonstrated that CA 19-9 was superior to CEA in post-operative follow-up (Samowitz et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Primary tumor resection is recommended even for stage IV patients (Samowitz et al, 2007;Chew et al, 2012;Padman et al, 2013;Yoon et al, 2014). In a study by Moghimi-Dehkordi et al it was determined that a surgical intervention targeting primary tumors was significantly associated with survival in univariate analysis but this significance diminished in multivariate analysis, leading to not being considered an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…23 Finally, TP53, a gatekeeper gene that controls cell cycle arrest and apoptosis, is mutated in 20-40% of colorectal cancers. 24,25 Expression of functional p53 is important in the prevention of cancer development from precancerous lesions, 26 and mutations of p53 frequently occur together with mutations of tumor-suppressor genes or of proto-oncogenes. 24 Thus, in colorectal cancer, the 4 signaling pathways-wnt, Ras/MAPK, PI3K and p53-each contribute to important aspects of tumorigenesis and act in concert during tumor development.…”
Section: Uiccmentioning
confidence: 99%
“…24,25 Expression of functional p53 is important in the prevention of cancer development from precancerous lesions, 26 and mutations of p53 frequently occur together with mutations of tumor-suppressor genes or of proto-oncogenes. 24 Thus, in colorectal cancer, the 4 signaling pathways-wnt, Ras/MAPK, PI3K and p53-each contribute to important aspects of tumorigenesis and act in concert during tumor development.Our increased understanding of the processes that lead to cancer development has shifted the focus of new cancer therapies to targeted interventions, which attempt to block selectively the pathways activated by the genetic mutations present in individual cancers. 27,28 Given the complexity of the genetic changes present in cancer, and the still incomplete knowledge of how different pathways interact to establish and maintain tumors, much of the development phase relies on ''in vitro'' model systems.…”
mentioning
confidence: 99%
“…Obecnie oczywiste jest, że istnieje wiele szlaków prowadzących do powstania nowotworu w tym narządzie. Okazało się bowiem, że tylko ok. 10% nowotworów jelita ma mutacje w trzech "klasycznych" genach modelu Fearona-Vogelsteina: APC, KRAS i P53 [15]. Dlatego powstały kolejne wersje ogólnych modeli kancerogenezy: jedną z najczęściej cytowanych prac podsumowujących aktualny stan wiedzy w tej dziedzinie jest praca Hanahana i Weinberga [16].…”
Section: Implikacje Modelu Fearona-vogelsteinaunclassified